57 The Use of a Hemi Glabella Flap for Reconstruction of Medial Canthus Defects. (4th May 2021) - Tan, P; Agilinko, J; Khalil, A
Abstract: Background: Medial canthal reconstruction is a challenging task due to the complex anatomy. The glabellar flap is a common viable technique; however, this results in narrowing of the eyebrows, bulky nasal dorsum and horizontal scarring which is aesthetically displeasing. The senior author in this paper has developed an intuitive modification to the technique. Method: A rotational advancement flap involving the upper lateral nasal wall with the hemi glabella was formed and transferred to the medial canthal defect. The donor site was closed in a V-Y manner. Complete closure of defect was achieved in all patients. Results: Reconstruction using the Hemi-Glabellar technique was performed on 12 patients following resection of BCC in or near the medial canthus area. Superficial cellulitis was noted in 2 patients, they were managed oral antibiotics. There was bruising in 7 patient which resolve spontaneously in 4-7 days. All patients had a good outcome at 2 months and 6 months follow up. There was no flap loss and all patients were satisfied with the aesthetic outcome. Conclusions: The technique highlighted can be performed easily and is applicable to reconstruction to defects of the medial canthus with excellent aesthetic outcomes with an inconspicuous scar and supple skin with matching colour